Oral hygiene and periodontal status in the primitive hidden tribe of Patalkot, a tribal area in Central India - Arpan Shrivastav; Rajkumar Maurya; Chandresh Shukla; Trilok Sahu; Neeraj Chauhan; Antriksh Azad; Ashutosh Dubey (Wolters Kluwer Medknow Publications, 2018)
Introduction: Very little is known about the hard to reach tribal communities in India and one such community is a primitive hidden and isolated tribe group of Bharia people in Patalkot. Their health problems need special attention as they have very limited access to health care. The aim of this study is to assess the oral hygiene and periodontal status in the primitive tribe group of Bharias in Patalkot, Madhya Pradesh, India. Materials and Methods: A descriptive cross-sectional study was undertaken with sample size of 462 patients. The sample was selected using simple random technique. A predefined pro forma was used to record information about oral hygiene practices and tobacco-related habits. Oral Hygiene Index-simplified (OHI-S), Community Periodontal Index (CPI), and loss of attachment (LOA) were used to assess oral hygiene and periodontal status, respectively. Results: The prevalence of periodontal disease based on CPI scores showed that 35.4 % had periodontal pocket > 6mm. It was also found that 27.9% people had attachment loss of 6-8mm. Mean Debris Index-simplified, Calculus Index-simplified, and OHI-S for the participants were 1.59 ± 0.73, 0.99 ± 0.70, and 2.56 ± 1.36, respectively. Poor oral hygiene status was found in 36.3% of Bharias. Conclusion: Higher prevalence of periodontal diseases and poor oral hygiene status in Bharia people can be attributed mainly to their difficult terrain, isolation, very low literacy level, socioeconomic status, and cultural practices.